Effect of auxin types on in vitro and ex vitro rooting and acclimatization of grapevine as influenced by substrates - Barreto, M. S.; Nookaraju, A. (Indian Journal of Horticulture, 2007)
Transferring micropropagated plantlets from in vitro to in vivo conditions is a critical step because plantlets have under-developed cuticle and stomata which result in wilting due to low humidity, fungal attack and bleaching in high light intensities. The resumption of terminal growth indicates successful establishment which is a change from mixotrophy to autotrophy. The survival of Vitis vinifera cvs. 2A-Clone and Red Globe plantlets rooted in vitro was 86.66 and 83.33%, respectively and the established plants showed a well-defined root system. Plantlets rooted in vivo by auxin pulse were easier to transfer and acclimatize with a survival percentage of 96.66 and 79.92 for 2A-Clone and Red Globe, respectively but the rooting was of fibrous type with few main roots and less number of root hairs. Coco-peat in combination with sand and soil was better for quick acclimatization and establishment (97.5 and 95% survival for 2A-Clone and Red Globe respectively) of the micropropagated plantlets.
Keywords: auxin pulse; coco-peat; grape; micropropagation; plantlet survival

Variability among vitis vinifera cultivars to in vitro propagation - Barreto, M. S.; Nookaraju, A.; Joglekar, A. M.; Karibasappa, G. S.; Agrawal, Dinesh C. (Proceedings of the International Symposium on Grape Production and Processing, 2008)
Response of grapevines to tissue culture has been reported to be genotype dependent, hence it becomes imperative to optimize culture conditions for newly developed varieties or cultivars, needing a large scale planting but availability of sufficient planting stock is a constraint. In the present study, conditions for in vitro propagation of six popular table grape cultivars have been standardized. Single node stem segments of cultivars 2A-Clone of Thompson Seedless, Red Globe, Crimson Seedless, Thompson Seedless, Flame Seedless and Italia cultured on ten different basal media showed varied percentages of bud break and morphogenetic responses. The percentage of bud break varied among the six cultivars. Direct rooting at basal ends of single node segments was observed in all the cultivars except in Italia. Woody plant medium induced the highest response and Eriksson medium the least in all the cultivars tested. Rooted nodal segments with shoots in axils could be established into whole plants on potting. Six cultivars showed different optimum concentrations of growth regulators for induction of maximum number of multiple shoots in both primary as well as secondary nodal segments. Shoot proliferation could be enhanced by several fold in the majority of cultivars on culture of initial shoot clumps to glass bottles instead of culture tubes. Six cultivars showed significant differences in optimum requirement of nutrients and growth regulators for shoot elongation, in vitro and ex vitro rooting and survival rate. Tissue culture plants of all the six cultivars could establish successfully in a greenhouse.
International Symposium on Grape Production and Processing, Baramati, INDIA, FEB 06-11, 2006
Keywords: basal media; Grapevine; growth regulators; micropropagation; Tissue culture; Vitis